Metal Ion-Exchanged Bentonites as Useful Solid Catalysts for Regioselective Nitration of Toluene - Zhang, H.; Peng, X.; Zhao, S. (Asian Journal of Chemistry, 2013)
Metal ion-exchanged bentonites were found to be efficient catalysts in regioselective nitration of toluene when using nitric acid as nitrating agent. Fifteen metal ion-exchanged bentonites were tested as catalysts toward a para position considerably. Out of a range of catalysts tried silver-supported bentonite appeared of higher regioselectivity of ortho-para ratio of 0.64 in an acceptable yield of 45 %. The possible recovery and reuse of catalyst suggest that system would be commercially viable.